2012
DOI: 10.1002/nla.1806
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the wave number dependency of the convergence rate of a multigrid preconditioned Krylov method for the Helmholtz equation with an absorbing layer

Abstract: SUMMARY This paper analyzes the Krylov convergence rate of a Helmholtz problem preconditioned with multigrid. The multigrid method is applied to the Helmholtz problem formulated on a complex contour and uses the generalized minimal residual method as a smoother substitute at each level. A one‐dimensional model is analyzed both in a continuous and discrete way. It is shown that the Krylov convergence rate of the continuous problem is independent of the wave number. The discrete problem, however, can deviate sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 22 publications
5
18
0
Order By: Relevance
“…Upon reaching this maximum, the number of iterations decreases slowly, exhibiting a steep descend for values of σ around − 8 ∕ h 2 . The same observation has been reported in , where an eigenvalue analysis was performed to rigourously anticipate the Krylov convergence behaviour. Note that we have used standard Dirichlet boundary conditions, as opposed to the absorbing boundary conditions used in ; however, the conclusions are identical.…”
Section: Numerical Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Upon reaching this maximum, the number of iterations decreases slowly, exhibiting a steep descend for values of σ around − 8 ∕ h 2 . The same observation has been reported in , where an eigenvalue analysis was performed to rigourously anticipate the Krylov convergence behaviour. Note that we have used standard Dirichlet boundary conditions, as opposed to the absorbing boundary conditions used in ; however, the conclusions are identical.…”
Section: Numerical Resultssupporting
confidence: 72%
“…The same observation has been reported in , where an eigenvalue analysis was performed to rigourously anticipate the Krylov convergence behaviour. Note that we have used standard Dirichlet boundary conditions, as opposed to the absorbing boundary conditions used in ; however, the conclusions are identical. The large difference in the number of Krylov iterations required is due to the indefinite nature of the problem, reaching a maximum around σ = − 4 ∕ h 2 (where the problem is heavily indefinite and thus hard to solve) and causing the number of iterations to suddenly drop for values of σ around − 8 ∕ h 2 , that is, where the 2D problem turns negative definite (and thus again easy to solve), as Figure (b) clearly illustrates (see colours).…”
Section: Numerical Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Note that for all methods, good scalability in function of the wavenumber k (referred to as ‘ k ‐scalability’) is de facto not guaranteed. The rising computational cost of MG–GMRES with ECS boundaries in function of k was explained in by pointing out that the convergence rate behaves asymptotically when nearing k 2 = 4 ∕ h 2 (independently of the problem dimension). A comparable argument explains the similarly poor k ‐scalability for the level‐dependent MG scheme.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…In , Reps et al analyze the Krylov convergence rate of a Helmholtz problem preconditioned with multigrid, which is applied to the Helmholtz problem formulated on a complex contour and uses polynomial smoothers at each level. For a one‐dimensional model, it is shown that the Krylov convergence rate of the continuous problem is independent of the wave number.…”
mentioning
confidence: 99%